2019
DOI: 10.1021/acsabm.8b00709
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Nanoceria Structures as Enzyme Mimetic Agents: The Role of Bodily Electrolytes on Maximizing Their Activity

Abstract: Nanoceria, typically used for 'clean air' catalytic converter technologies, is the same material that could also be used as a nanomedicine. Specifically, nanoceria, which can capture, store and release oxygen, for oxidative/reductive reactions, can also be used to control oxygen content in cellular environments; as a 'nanozyme', nanoceria mimics enzymes by acting as an antioxidant agent. The computational design procedures for predicting active materials for catalytic converters can therefore be used to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 74 publications
5
37
0
Order By: Relevance
“…Cerium can reversibly bind oxygen and shift between oxidation states Ce 4+ and Ce 3+ , giving the nanoparticle a regenerative capacity to act cyclically as a superoxide dismutase mimetic, which is associated with higher Ce 3+ concentrations, and a catalase mimetic, which is associated with higher Ce 4+ concentrations, depending on the particle size and redox environment [19,20]. Particle size plays a role in the ratio of Ce 3+ and Ce 4+ present in CeNPs in that as particle size decreases, Ce 3+ content increases while Ce 4+ declines [23,70,71,72,73]. Different analytical methods used to assess the Ce 3+ concentration of CeNPs have yielded varying results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerium can reversibly bind oxygen and shift between oxidation states Ce 4+ and Ce 3+ , giving the nanoparticle a regenerative capacity to act cyclically as a superoxide dismutase mimetic, which is associated with higher Ce 3+ concentrations, and a catalase mimetic, which is associated with higher Ce 4+ concentrations, depending on the particle size and redox environment [19,20]. Particle size plays a role in the ratio of Ce 3+ and Ce 4+ present in CeNPs in that as particle size decreases, Ce 3+ content increases while Ce 4+ declines [23,70,71,72,73]. Different analytical methods used to assess the Ce 3+ concentration of CeNPs have yielded varying results.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been written about the effect of phosphate on the catalytic activity of CeNPs [90,91]. Phosphate ions poison superoxide dismutase-mimetic activity of CeNPs [73], and phosphate is present in virtually all physiological solutions in low, millimolar concentrations. Phosphate diminishes superoxide dismutase-mimetic activity by binding to the surface of the CeNP crystals at the sites of oxygen vacancies, and there is a direct relationship between the Ce 3+ concentration and the number of oxygen vacancies, as noted above.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that phosphate anions can strongly bind to (100) surfaces, inhibiting the oxygen capture and release, hence poisoning the ceria nanozyme. By contrast, the phosphate interaction with (111) surfaces is weaker, therefore these surfaces protect the ceria nanostructure against passivation [29]. 111), (110), and (100) surfaces.…”
Section: Ceria Nanomorphology-reactivity Relationshipmentioning
confidence: 99%
“…Ce (IV) is white, Ce (III) is blue, and oxygen is red. Reprinted with permission from [ 29 ], Copyright © 2021, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…This is in agreement with previous computational work. 41,47,48 The surface energy for the reduced surface was calculated according to…”
Section: Surface Energies and Thermodynamic Frameworkmentioning
confidence: 99%